Sample size requirements for one-year treatment effects using deep gray matter volume from 3T MRI in progressive forms of multiple sclerosis. (2nd November 2017) - Kim, Gloria; Chu, Renxin; Yousuf, Fawad; Tauhid, Shahamat; Stazzone, Lynn; Houtchens, Maria K.; Stankiewicz, James M.; Severson, Christopher; Kimbrough, Dorlan; Quintana, Francisco J.; Chitnis, Tanuja; Weiner, Howard L.; et al.
ABSTRACT: Objective: The subcortical deep gray matter (DGM) develops selective, progressive, and clinically relevant atrophy in progressive forms of multiple sclerosis (PMS). This patient population is the target of active neurotherapeutic development, requiring the availability of outcome measures. We tested a fully automated MRI analysis pipeline to assess DGM atrophy in PMS. Design/Methods: Consistent 3D T1-weighted high-resolution 3T brain MRI was obtained over one year in 19 consecutive patients with PMS [15 secondary progressive, 4 primary progressive, 53% women, age (mean±SD) 50.8±8.0 years, Expanded Disability Status Scale (median, range) 5.0, 2.0–6.5)]. DGM segmentation applied the fully automated FSL-FIRST pipeline (http://fsl.fmrib.ox.ac.uk ). Total DGM volume was the sum of the caudate, putamen, globus pallidus, and thalamus. On-study change was calculated using a random-effects linear regression model. Results: We detected one-year decreases in raw [mean (95% confidence interval): –0.749 ml (–1.455, –0.043), p = 0.039] and annualized [–0.754 ml/year (–1.492, –0.016), p = 0.046] total DGM volumes. A treatment trial for an intervention that would show a 50% reduction in DGM brain atrophy would require a sample size of 123 patients for a single-arm study (one-year run-in followed by one-year on-treatment). For a two-arm placebo-controlled one-year study, 242 patients would be required per arm. The use of DGM fraction required more patients. The thalamus, putamen, and globus pallidus, showed smaller effect sizes in their on-study changes than the total DGM; however, for the caudate, the effect sizes were somewhat larger. Conclusions: DGM atrophy may prove efficient as a short-term outcome for proof-of-concept neurotherapeutic trials in PMS.